Loop-seal flow characteristics of a circulating fluidized bed for 3 MWth scale chemical looping combustion system. (1st July 2023) - Kim, Daewook; Won, Yooseob; Hwang, Byung Wook; Kim, Jae Young; Kim, Hana; Choi, Yujin; Lee, Yu-Ri; Lee, Seung-Yong; Jo, Sung-Ho; Park, Young Cheol; Baek, Jeom-In; Nam, Hyungseok; et al.
Abstract: This study aimed to provide a design and operational approach for a loop-seal, which is the heart of a circulating fluidized bed (CFB). Thousands of CFB systems use this non-mechanical valve to optimize performance by controlling the solids circulation rate while preventing gas mixing between reactors. Nevertheless, its design and operating guidance remains unclear because of its intricate flow characteristics, causing confusion in design and operation of the entire CFB. This study experimentally investigated the three most important elements while designing and operating loop-seal: conditions for initiating solids flow, the maximum obtainable solids flow rate, and quantitative control of solids flow rate. Experiments were conducted in a CFB, which simulated 3 MWth chemical looping combustion (CLC) system that is currently being developed. The onset of solids flow occurs when the gas drag force in horizontal passage overcomes the resistance force generated by the bed of particles. The maximum solids circulation rate was determined by solids height in the supply chamber and pressure around CFB loop. A correlation for quantitative control of solids flow in loop-seal was proposed by the relationship between the gas drag force and particle velocity. Finally, operational conditions for the loop-seal in 3 MWth CLC were proposed. Graphical abstract: Figure: Operating conditions of the loop-seal in 3 MWth chemical looping combustion system derived in this study. Image 1 Highlights: Flow characteristics in loop-seal was analyzed and design factors were confirmed. Solid flow started after overcoming resistance force by solid in horizontal path. Particle velocity in horizontal path increased linearly by drag force of gas. Solid height in standpipe determined the maximum solid circulation rate. 3 Nm 3 /hr of Qsup, in was required for solid circulation of 15 kg/s in 3 MWth CLC.